Preoperative Fasting Abbreviation and its Effects on Postoperative Nausea and Vomiting Incidence in Gynecological Surgery Patients - Marquini, Gisele Vissoci; Pinheiro, Francisco Edes da Silva; Vieira, Alfredo Urbano da Costa; Pinto, Rogério Melo da Costa; Uyeda, Maria Gabriela Baumgarten Kuster; Girão, Manoel João Batista Castello; Sartori, Marair Gracio Ferreira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To investigate the effects of preoperative fasting abbreviation with a carbohydrate and protein-enriched solution, on postoperative nausea and vomiting (PONV) incidence in gynecological surgery patients, a population naturally at risk for such unpleasant episodes.Methods The present prospective double-blind randomized study was performed at The Hospital Municipal e Maternidade Dr. Odelmo Leão Carneiro (HMMOLC, in the Portuguese acronym), in Uberlândia, state of Minas Gerais, Brazil, in partnership with the Gynecology Department of the Universidade Federal de São Paulo (UNIFESP), approved by the Human Research Ethics Committee of UNIFESP and the board of HMMOLC, and included in the Brazil Platform and in the Brazilian Clinical Trial Registry. After signing the consent form, 80 women, who were submitted to gynecological surgery in the period from January to June 2016, were randomized into 2 groups: control group (n = 42) and juice group (n = 38). They received, respectively, 200 mL of inert solution or liquid enriched with carbohydrate and protein 4 hours presurgery. The incidence, frequency and intensity of PONV were studied using the Visual Analogue Scale (VAS), with statistical analysis performed by the software IBM SPSS Statistics for Windows, Version 20.0 (IBM Corp, Armonk, NY, USA).Results The incidence of nausea and vomiting was lower than in the literature, to this population, with 18.9% (14/74) for the control group and 10.8% (8/74) for the juice group, respectively, with no statistically significant difference between the groups.Conclusion The incidence of nausea and vomiting was lower than in the literature, but it cannot be said that this is due to the abbreviation of fasting. It can provide greater comfort, with the possibility of PONV prevention in patients at risk for these episodes.
Keywords: preoperative care; surgical procedures in gynecology; postoperative nausea and vomiting; carbohydrates; proteins; controlled random clinical trial